Cytochromes P450 in benzene metabolism and involvement of their metabolites and reactive oxygen species in toxicity - Gut, I; Nedelcheva, V; Soucek, P; Stopka, P; Tichavská, B (Environmental health perspectives, 1996)
Cytochrome P450 (CYP) 2E1 was the most efficient CYP enzyme that oxidized benzene to soluble and covalently bound metabolites in rat and human liver microsomes. The covalent binding was due mostly to the formation of benzoquinone (BQ), the oxidation product of hydroquinone (HQ), and was inversely related to the formation of soluble metabolites. In rats, inhalation of benzene (4 mg/liter of air) caused a rapid destruction of CYP2B1 previously induced by phenobarbital. The ability of benzene metabolites to destroy liver microsomal CYP in vitro decreased in the order BQ > HQ > catechol > phenol. The destruction was reversed by ascorbate and diminished by alpha-tocopherol, suggesting that HQ was not toxic, whereas BQ and semiquinone radical (SQ) caused the effect. In the presence of nicotinamide adenine dinucleotide phosphate, reduced (NADPH) the microsomes did not oxidize HQ to BQ, while the formation of superoxide anion radical from both HQ and BQ was markedly quenched. Destruction of CYP in vitro caused by HQ or BQ was not mediated by hydroxyl radical formation or by lipid peroxidation. On the contrary, HQ and BQ inhibited NADPH-mediated lipid peroxidation. Ascorbate induced high levels of hydroxyl radical formation and lipid peroxidation, which were differentially affected by quinones, indicating different mechanisms. Despite reducing the toxicity of HQ and BQ, ascorbate appeared to induce its own toxicity, reflected in high levels of lipid peroxidation. Iron redox cycling played a significant role in the NADPH-induced hydroxyl radical formation but not in that caused by ascorbate; however, lipid peroxidation induced by NADPH or ascorbate was suppressed by ethylenediaminetraacetate, indicating a crucial role of iron. Thus, the data indicate that the quinones destroyed CYP directly and not via oxygen activation or lipid peroxidation.
Keywords: Microsomes, Liver; DNA Damage; Rats; In Vitro Techniques; systém (enzymů) cytochromů P-450; hydrochinony; reaktivní formy kyslíku; proteiny; DNA Adducts; poškození DNA; Rats, Wistar; mužské pohlaví; benzen; techniky in vitro; Oxidation-Reduction; Cytochrome P-450 Enzyme System; krysa rodu Rattus; Reactive Oxygen Species; zvířata; Benzoquinones; Humans; Benzene; jaterní mikrozomy; oxidace-redukce; benzochinony; potkani Wistar; Hydroquinones; adukty DNA; Cytochrome P-450 CYP2E1; cytochrom P-450 CYP2E1; Proteins; lidé; Male; Animals